Diagnostic performance of mid-upper arm circumference to identify overweight and obesity in children and adolescents: a protocol for a systematic review and meta-analysis. Issue 3 (31st March 2021) - Sisay, Binyam Girma; Hassen, Hamid Yimam; Gebreyesus, Seifu Hagos
Abstract : Introduction: Mid-upper arm circumference (MUAC) has been suggested as an alternative screening tool to identify overweight and obesity in children and adolescents. Several studies have examined the diagnostic performance of MUAC to identify overweight and obesity in children and adolescents. However, the existing literature shows a considerable variability in measures of diagnostic performance and hence makes it difficult to direct clinical and public health practice. Therefore, this systematic review and meta-analysis aimed to synthesise evidence on the performance of MUAC to identify overweight and obesity in children and adolescents. Methods and analysis: A systematic search of databases including PubMed, EMBASE, SCOPUS, Cochrane Database of Systematic Reviews, Cochrane CENTRAL, Web of Science, CINAHL and PsycINFO will be conducted. The search will cover all studies until 1 April 2021. Grey literature will also be retrieved from Google Scholar. Titles and abstracts will be screened by two independent reviewers. The Quality Assessment of Diagnostic Accuracy Studies 2 tool will be used to assess the risk of bias and clinical applicability of each study. To assess possible publication bias, we will use Deeks' funnel plot. We will investigate the sources of heterogeneity by visual inspection of the paired forest plots and summary receiver operating characteristic plots. The pooled summary statistics for the area under the curve, sensitivities, specificities, likelihood ratios and diagnostic ORs with 95% CI will be reported. Ethics and dissemination: The underlying study is based on published articles thus does not require ethical approval. The findings of the systematic review and meta-analysis will be published in a peer-reviewed journal and disseminated in different scientific conferences and seminars. PROSPERO registration number: CRD42020183148.